Drought and Retribution : Evidence from a Large-Scale Rainfall-Indexed Insurance Program in Mexico - Fuchs, Alan; Wolff, Hendrik (World Bank, Washington, DC, 2016)
Although weather shocks are a major source of income fluctuation, most of the world's poor lack insurance coverage against them. Absence of formal insurance contributes to poverty traps, as investment decisions are conflicted with risk management ones: risk-averse farmers tend to underinvest and produce lower yielding yet safer crops. In the past few years, weather index insurance has gained increasing attention as an effective tool to provide small-scale farmers coverage against aggregate shocks. However, there is little empirical evidence about its effectiveness. This paper studies the effect of the recently introduced rainfall-indexed insurance on farmers' productivity, risk management strategies, as well as per capita income and expenditure in Mexico. The identification strategy takes advantage of the variation across counties and across time in which the insurance was rolled-out. The analysis finds that the presence of insurance in treated counties has significant and positive effects on maize productivity. Similarly, there is a positive association between the presence of insurance in the municipality and rural households' per capita expenditure and income, although no significant relation is found between the presence of insurance and the number of hectares destined for maize production.